Comparative evaluation of three different an obturating materials in pulpectomy; An in vivo study - Chanchal Goinka; Kola Srikanth Reddy; Aruna Ganapathi; K Harshitha Nallagula; Alekya Kondapaneni; V V N. Sunil (Wolters Kluwer Medknow Publications, 2020)
Objectives: The aim of this study was to clinically evaluate, radiographically zinc oxide eugenol (ZOE) paste, metapex, and Alo vera gel with zinc oxide powder as root canal filling material in primary teeth. Methodology: In the present study, pulpectomies were performed on 51 primary second molar in 55 children, aged between 4 and 9 years, of these, 24 children were randomly divided into three groups of 17 teeth each selected for endodontic treatment. Obturation was done with a mixture of ZOE paste, metapex and A. vera gel with ZOE powder. Clinical, radiographic evaluation was done after 3 months, 6 months, and 12 months. Data were analyzed using Fisher's exact test and Cochran's Q-test, and the value of P was set at 0.05. Results: The three pastes achieved convergent clinical and radiographic success within the three observation periods (P > 0.05). ZOE paste was the slowest in its resorption. Conclusion: Zinc oxide powder with A. vera gel can be used as alternatives to ZOE and metapex.